2019
DOI: 10.1038/s41581-019-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation in health and disease

Abstract: The glycom e describes the complete repertoire of glycoconjugates com posed of carbohydrate chains, or glycans, that are covalently linked to lipid or protein molecules. Glycoconjugates are formed through a process called glycosylation and can differ in their glycan sequences, the connections between them and their length. Glycoconjugate synthesis is a dynamic process that depends on the local milieu of enzymes, sugar precursors and organelle structures as well as the cell types involved and cellular signals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
1,209
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,365 publications
(1,227 citation statements)
references
References 268 publications
(256 reference statements)
10
1,209
0
8
Order By: Relevance
“…These results indicate the N-glycan compositions and types on S protein largely attribute to different host cells with the differential processing pathways of glycosylation. We can expect that the native N-glycosylation profile of the SARS-CoV-2 S protein in humans tends to be consistent with that of the recombinant protein expressed in human cells, unless the virus buds off early in the glycosylation processing pathway and produces immature glycans (19,27,35). Intriguingly, the immature N-glycans such as high-mannose are regarded as "non-self" glycans (35, 36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate the N-glycan compositions and types on S protein largely attribute to different host cells with the differential processing pathways of glycosylation. We can expect that the native N-glycosylation profile of the SARS-CoV-2 S protein in humans tends to be consistent with that of the recombinant protein expressed in human cells, unless the virus buds off early in the glycosylation processing pathway and produces immature glycans (19,27,35). Intriguingly, the immature N-glycans such as high-mannose are regarded as "non-self" glycans (35, 36).…”
Section: Discussionmentioning
confidence: 99%
“…Glycosylation of proteins is intricately processed by various enzymes coordinated in the endoplasmic reticulum and Golgi apparatus. The glycan composition and structure decoration at specific sites occurred in a non-templated manner governed by host cells, thus frequently resulting in a heterogeneous glycan occupancy on each glycosite (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycans are one of the most vital components of a cell (Ajit, 2017). The glycan, components of glycoconjugates, is formed through the glycosylation process and mediates many physiological and pathological functions (Reily, Stewart, Renfrow, & Novak, 2019). Many studies reported that glycosylation is involved in many crucial biological processes, e.g., receptor activation, molecular traff icking and clearance, signal transduction, cell adhesion, endocytosis, and host-pathogen interactions (Hyono, Mazda, Okazaki, Tadokoro, & Ohshima, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that glycosylation is involved in many crucial biological processes, e.g., receptor activation, molecular traff icking and clearance, signal transduction, cell adhesion, endocytosis, and host-pathogen interactions (Hyono, Mazda, Okazaki, Tadokoro, & Ohshima, 2008). Glycosylation plays a crucial part in many cellular mechanisms of both health and disease, such as tumor cell formation and metastatic diseases (Cadena, Cushman, & Welsh, 2018;Nardy, Freire-de-lima, Freire-de-lima, & Morrot, 2016), viral immune escape, inflammatory responses, and kidney functions (Reily et al, 2019).…”
Section: Introductionmentioning
confidence: 99%